Gas Separation Properties of Polyimide Thin Films on Ceramic Supports for High Temperature Applications - Sara Escorihuela; Alberto Tena; Sergey Shishatskiy; Sonia Escolástico; Torsten Brinkmann; Jose Manuel Serra; Volker Abetz (Membranes, 2018)
Novel selective ceramic-supported thin polyimide films produced in a single dip coating step are proposed for membrane applications at elevated temperatures. Layers of the polyimides P84®, Matrimid 5218®, and 6FDA-6FpDA were successfully deposited onto porous alumina supports. In order to tackle the poor compatibility between ceramic support and polymer, and to get defect-free thin films, the effect of the viscosity of the polymer solution was studied, giving the entanglement concentration (C*) for each polymer. The C* values were 3.09 wt. % for the 6FDA-6FpDA, 3.52 wt. % for Matrimid®, and 4.30 wt. % for P84®. A minimum polymer solution concentration necessary for defect-free film formation was found for each polymer, with the inverse order to the intrinsic viscosities (P84® ≥ Matrimid® >> 6FDA-6FpDA). The effect of the temperature on the permeance of prepared membranes was studied for H2, CH4, N2, O2, and CO2. As expected, activation energy of permeance for hydrogen was higher than for CO2, resulting in H2/CO2 selectivity increase with temperature. More densely packed polymers lead to materials that are more selective at elevated temperatures.